COVID-19 and Labour Law: Ireland - David Mangan (Italian Labour Law e-Journal, 2020)
Similar to many other European countries, businesses in Ireland are largely working remotely if they are not shut temporarily (with the exception of food stores and pharmacies). The government has implemented a plan for businesses and workers (including the self-employed) centring on income support. Many questions remain to be openly discussed such as when businesses may start to re-open, how this may be done safely; not to mention the longer term impact.